Peranan Dana Bantuan Sosial Terhadap Kualitas Rumah Masyarakat Miskin Melalui Program Bedah Rumah di Kelurahan Watallipue Kec. Tempe Kab. Wajo - Syahida Syahida; Andi Temmanengnga; Andi Yuniarti; Hasna Hasna (Institute of Advanced Knowledge and Science, 2023)
This research aims to determine the role of social assistance funds on the quality of poor people's houses through a house renovation program in Watallipue Village, Tempe District, Wajo Regency. The population in this study were all recipients of the house renovation program assistance in Watallipue Village. Sample A total of 50 people. Sampling used a sampling technique using a purposive sampling technique. This research is about the role of social assistance funds on the quality of poor people's houses through a house renovation program in Watallipue Village, Tempe District, Wajo Regency, using qualitative methods where data collection is carried out by interviews so as to dig deeper into social assistance funds and house quality. The results obtained in this research were that there was an improvement in the quality of people's houses from before the house renovation program was carried out. These places could be said to be uninhabitable due to leaking roofs and walls that leaked when it rained. However, after carrying out a house renovation program, the place became a place that was considered habitable.